Good clean governance (GCG) dalam kepemimpinan Basuki Tjahaja Purnama (Ahok) sebagai Gubernur DKI Jakarta ditinjau dari perspektif asta brata - A.S. Kobalen; Andi Faisal Bakti (Universitas Merdeka Malang, 2019)
Public sector leadership in Indonesia has always been an issue that is at the center of the attention of the Indonesian people. This has emerged since the reformation (1998) which gave birth to many leaders who were not found in the New Order era. This study uses a qualitative approach. Data sources are generated from literature (literature) interviews, documentation, and observations. Data analysis techniques use analytical techniques from Miles, Huberman, and Saldana, which require components of analytical techniques whose data consists of data condensation, data presentation (data display) and drawing conclusions / verification (drawing and verifying Conclusion). The results are seen in 5 GCG perspectives of Andi Faisal Bakti (2000) and 8 principles of Asta Brata (Kakawin Ramayana). It was generally found that the leadership of Basuki Tjahaja Purnama (BTP / Ahok) as Governor of DKI Jakarta was very contradictory to the principle of ASA Brata (sun, moon, wind, wealth, ocean, fire, death, and rain) based on a GCG perspective that characterizes transparency, consistency, agility, accountability, and communicability.DOI: https://doi.org/10.26905/pjiap.v4i1.2272